Volatility shifts and persistence in variance: Evidence from the sector indices of Istanbul Stock Exchange - Efe Çağlar Çağli; Pınar Evrim Mandacı; Hakan Kahyaoğlu (International Journal of Economic Sciences and Applied Research, 2011)
This study examines the impact of volatility shifts on volatility persistence for three major sector indices of Istanbul Stock Exchange (ISE) and ISE National 100 index over the period beginning from 1997 and ending in 2009. The exponential generalized autoregressive conditional heteroskedasticity (EGARCH) model is extended by taking account of the volatility shifts which are determined by using iterated cumulative sums of squares (ICSS) and modified ICSS algorithms such as Kappa-1 (ê-1) and Kappa-2 (ê-2). The results indicate that the inclusion of volatility shifts in the model substantially reduces volatility persistence and suggest that the sudden shifts in volatility should not be ignored in modelling volatility for Turkish sector indices.
Keywords: C22; C52; C58; 330; stock return volatility; volatility shifts; persistence; Turkish stock market